1991
DOI: 10.1107/s0108270191005048
|View full text |Cite
|
Sign up to set email alerts
|

Structure of hexaaquacopper(II) bromate

Abstract: Abstract.[Cu(H20)6](BrO3)2, M,=427"44, cubic, Pa-3, a = 10.3240 (6) A, V = 1100.38 (4) A 3, Z = 4, Dx=2"580gcm -3, A(MoK~)=0.71073A, /~= 92.32 cm-l, F(000) = 828, T = 296 K, R = 0.038 for 336 unique reflections having I > trz. The single type of copper ion (site symmetry 3) is coordinated by six water-molecule O atoms, each at an observed distance of 2-079 (4)A, in an array which is virtually regular octahedral, the nominal 90 ° angles measuring 89.95 (15) and 90.05 (15) °. Thus, this is not a typical Cu" comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 10 publications
(15 reference statements)
5
22
0
1
Order By: Relevance
“…[25] The high lability of the ligands is also a characteristic feature of the mercury(II) ion, even in complexes with two strong linear HgÀS bonds with thiol groups. [26,27] Recently, EXAFS studies showed that hexaaquacopper-(II) bromate and hexakis(pyridine 1-oxide)copper(II) perchlorate, reported in crystallographic studies to have six equidistant Cu À O bonds in space groups of high symmetry, [28,29] in reality contained Jahn-Teller-distorted, tetragonally elongated CuO 6 octahedra. [30] Hence, in such cases, www.chemeurj.org when the crystallographic space-group symmetry appears higher than the actual site symmetry of the individual complexes, the results become deceptive.…”
Section: Introductionmentioning
confidence: 98%
“…[25] The high lability of the ligands is also a characteristic feature of the mercury(II) ion, even in complexes with two strong linear HgÀS bonds with thiol groups. [26,27] Recently, EXAFS studies showed that hexaaquacopper-(II) bromate and hexakis(pyridine 1-oxide)copper(II) perchlorate, reported in crystallographic studies to have six equidistant Cu À O bonds in space groups of high symmetry, [28,29] in reality contained Jahn-Teller-distorted, tetragonally elongated CuO 6 octahedra. [30] Hence, in such cases, www.chemeurj.org when the crystallographic space-group symmetry appears higher than the actual site symmetry of the individual complexes, the results become deceptive.…”
Section: Introductionmentioning
confidence: 98%
“…All of the hydrogen bond angles (O-HÁ Á ÁO) in Cu(H 2 O) 6 (OPCy 3 ) 6 (BF 4 ) 2 are nearly 180°(179.49-179.74°), which has not been found before [3,4,8,10]. The hydrogen bond distance here (2.661-2.690 Å ) is shorter than others reported before 2.766(6)-3.248 Å [10] for Cu(ClO 4 ) 2 AE 6H 2 O, 2.672(3)-2.852(3) Å [8] for Cu(H 2 O) 6 (DPhP) 2 (Gly) 2 (2.709-2.841 Å ) [11] for Cu(NH 4 ) 2 (SO 4 ) 2 (H 2 O) 6 and (2.709(4)-3.245(4) Å ) [3] for Cu(H 2 O) 6 (BrO 3 ) 2 .…”
mentioning
confidence: 90%
“…For copper ion, because of its electronic d 9 configuration, a Jahn-Teller (JT) distortion is generally assumed to axially elongate two bonds of the octahedral CuðH 2 OÞ 2þ 6 complex which is described by [4 + 2]. But in fact, some hexaaquacopper ions are described by [2 + 2 + 2] [3,5,8,10,11] coordination, some even described by fivefold-coordination [1] or other [2]. One of the important effect that causes the departure from the strict JT structure of [4 + 2] is the surrounding units [9].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[19]) auf die Stärke der Wasserstoffbrücken zu beobachten sein. Ver gleicht man die intermolekularen Donor-AkzeptorAbstände 0 -0 (A/(Br03)-,-6H-,0; Co: 276,7(3), 280,0(3) pm [5]; Ni: 276,1(3), 280,6(3) pm [6]; Cu: 276,6(6), 279,8(5) pm) [7], läßt sich jedoch keine eindeutige Reihenfolge ableiten.…”
Section: Schwingungsspektrenunclassified